Optimal aerodynamic design of multi-flapping wing vehicles with morphing capabilities - Billingsley, Ethan; Ghommem, Mehdi; Vasconcellos, Rui [UNESP]; Abdelkefi, Abdessattar; AIAA (Amer Inst Aeronautics & Astronautics, 2021)
Some groups of birds have the ability to save energy during flight by arranging themselves in V-formation. This formation enables an increase in the overall efficiency of the group because the wake vortices shed by each of the birds provides additional lift and thrust to every member. Therefore, such flight arrangement is useful to consider during the design process of micro air vehicles. One significant difference when comparing the anatomy of birds to the design of most micro air vehicles is that bird wings are not completely rigid. Birds have the ability to both twist and bend their wings throughout the flapping cycle. Given these aspects of avian flight, the objective of this work is to incorporate active bending and torsion into an unsteady vortex lattice method simulation of multiple pairs of flapping wings arranged in V-formation. The goal is to incorporate wing morphing into the simulations by using bending and torsional mode shapes of a cantilever beam and to test a range of V-formation angles for a 3-member group size in order to determine the optimal configuration that leads to maximum propulsive efficiency. Results demonstrate that coupled bending and twisting of the first mode shape yields the highest propulsive efficiency over a range of formation angles. These results indicate the potential improvement in the aerodynamic performance of the formation flight when introducing active morphing.